Metabolomic profiling unravels the role of sphingolipid pathways in spot blotch resistance in wheat - Yadav, Sagar; Maiti, Saborni; Mundhe, Swapnil; Kadoo, Narendra (Acta Physiologiae Plantarum, 2025)
Spot blotch, caused by the soil- and air-borne fungal pathogen Bipolaris sorokiniana, is a major threat to wheat production. The disease is reaching epidemic proportions in wheat-growing areas, particularly in South Asia, South America, Africa, and Australia. In India, over 25 million hectares of wheat-growing area is threatened by this disease. A systematic study of metabolites can provide insights into the molecular basis of this disease. In the present study, we evaluated the impact of B. sorokiniana inoculation on two wheat varieties, Chirya3 (resistant to spot blotch) and DDK1025 (susceptible to spot blotch). We performed time-course non-targeted metabolite profiling of the pathogen-inoculated and mock-inoculated plants using liquid chromatography coupled with high-resolution mass spectrometry (LC-HRMS). Multivariate analysis was performed to construct a comprehensive statistical workflow, which led to the defined ``metabolomic phenotypes''. Modeling by Orthogonal Projection to Latent Structures-Discriminant Analysis (OPLS-DA) revealed significant metabolites in responses of the resistant and susceptible varieties to pathogen inoculation. A total of 699 metabolites displayed significant variations during the progression of infection. B. sorokiniana-inoculated Chirya3 exhibited high levels of some metabolites, such as sphingolipids, cysteine, phenylalanine, shikimates, etc. The study revealed that sphingolipid pathways are critical in resistance mechanisms contributing to enhanced lignification and disease resistance in wheat.
Keywords: Cochliobolus sativus; High-resolution mass spectrometry; LC-HRMS; Metabolite profiling; OPLS-DA; plant-pathogen interaction